IMPLEMENTASI HYPOTHETICAL LEARNING TRAJECTORY STATISTIKA BERBASIS REALISTIC MATHEMATICS EDUCATION UNTUK PEMAHAMAN KONSEP SISWA - Wibowo, Eko Ari; Rusdijanto, Titania Alya; Mairina, Upik; Setyaningsih, Nining; Sutarni, Sri (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
This study aims to identify the role of RME-based statistics HLT implementation in students' concept understanding ability at SMP Muhammadiyah 1 Kartasura class VIII in the odd semester of the 2024/2025 academic year. The method used was Didactical Design Research with a qualitative approach. The research focused on three research subjects, namely students with high (S1), medium (S2), and low (S3) concept understanding abilities. The results showed that the implementation of RME-based HLT contributed positively to students' understanding of statistics concepts. The learning process through the stages of HLT, namely emergent, model-for, model-of, and formal, facilitated students in building concept understanding gradually. S1 showed the ability to interpret data and relate it to real contexts well, S2 was able to understand basic concepts and apply them in similar problems, while S3 experienced an increase in understanding even though they still needed further guidance in applying concepts to more complex situations. This research indicates that the RME-based HLT is effective in facilitating the understanding of statistical concepts of students with different ability levels.